2023
DOI: 10.1021/jacsau.2c00646
|View full text |Cite
|
Sign up to set email alerts
|

Highly Charged Proteins and Their Repulsive Interactions Antagonize Biomolecular Condensation

Abstract: Biomolecular condensation is involved in various cellular processes; therefore, regulation of condensation is crucial to prevent deleterious protein aggregation and maintain a stable cellular environment. Recently, a class of highly charged proteins, known as heat-resistant obscure (Hero) proteins, was shown to protect other client proteins from pathological aggregation. However, the molecular mechanisms by which Hero proteins protect other proteins from aggregation remain unknown. In this study, we performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 86 publications
0
27
0
Order By: Relevance
“…This dual nature of IDRs can maintain the solubility of aggregation-prone proteins by shielding surface hydrophobic residues in solution and preventing insoluble aggregate formation. Alternatively, the polar and charged amino acids of IDRs can neutralize the surface charge of client proteins, protecting them from forming large aggregates connected by complementary charges (Tan et al, 2023). These interactions may explain the activity of Hero proteins in inhibiting the formation of disease-related protein aggregates commonly found in neurodegenerative diseases (Tsuboyama et al, 2020).…”
Section: Nondomain Biopolymers As Hydrotropes or Molecular Shieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…This dual nature of IDRs can maintain the solubility of aggregation-prone proteins by shielding surface hydrophobic residues in solution and preventing insoluble aggregate formation. Alternatively, the polar and charged amino acids of IDRs can neutralize the surface charge of client proteins, protecting them from forming large aggregates connected by complementary charges (Tan et al, 2023). These interactions may explain the activity of Hero proteins in inhibiting the formation of disease-related protein aggregates commonly found in neurodegenerative diseases (Tsuboyama et al, 2020).…”
Section: Nondomain Biopolymers As Hydrotropes or Molecular Shieldsmentioning
confidence: 99%
“…Because multivalent weak interactions may be lost during conventional biochemical purification of tightly associated complexes (e.g., washing steps during immunoprecipitation), proximity labeling methods such as Bio-ID or cross-linking immunoprecipitation will be required to investigate client or partner proteins of nondomain biopolymers. Considering that nondomain biopolymers typically do not form rigid structures and cannot be analyzed by conventional crystallography approaches, molecular dynamics (MD) simulations may also become indispensable tools in understanding the intricate behavior of these biomolecules, as has been shown for the analysis of the interaction between Hero11 and TDP43 (Tan et al, 2023).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The study by Tsuboyama et al has reported the ability of heat-resistant obscure (Hero) proteins to block the pathological aggregation of other proteins. Recently, such protective mechanism by the highly charged Hero proteins has been identified . It has been found that the Hero proteins not only reduce intermolecular contacts between its “client” proteins in the condensate phase but also prevent the proteins’ aggregation through binding with them and consequently exert electrostatic repulsion in the dilute phase.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, such protective mechanism by the highly charged Hero proteins has been identified. 39 It has been found that the Hero proteins not only reduce intermolecular contacts between its "client" proteins in the condensate phase but also prevent the proteins' aggregation through binding with them and consequently exert electrostatic repulsion in the dilute phase. Therefore, designing and developing systems capable of preventing pathogenic LLPS behavior under a wide range of conditions could become key in the future.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus the structure and dynamics of the condensates can be readily altered by various physiochemical factors or stimuli, such as pH, salt concentration, molecular crowding, protein folding/ligand binding, and post-translational modifications, which can potentially contribute to the regulation of cellular processes. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] The phase behavior can be further enriched by sequence segregation of IDRs, resembling the block copolymer, and by heterotypic inter-molecule interactions of multicomponent systems, which can often lead to the microphase separation and layered structures of condensates. 47 Nucleic acid molecules, which are highly charged, are key inducers or regulators of biological condensation mainly through inter-molecule Coulombic interactions.…”
Section: Introductionmentioning
confidence: 99%